On the Formal Integrability Problem for Planar Differential Systems - Antonio Algaba; Cristóbal García; Jaume Giné (Abstract and Applied Analysis)
We study the analytic integrability problem through the formal integrability problem and we show its connection, in some cases, with the existence of invariant analytic (sometimes algebraic) curves. From the results obtained, we consider some families of analytic differential systems in ℂ2, and imposing the formal integrability we find resonant centers obviating the computation of some necessary conditions.